Prevalensi dan karakteristik keluhan muskuloskeletal pada petani di Desa Aan Kabupaten Klungkung tahun 2018 - Luh Dindi Ayu Surya Kanti; Muliani Muliani; Yuliana Yuliana (Department of Anatomy, Medical Faculty, Universitas Udayana, Bali-Indonesia, 2019)
Background: Aan village is one of the villages where most of the people work as farmers. Farmer is one type of work that has a high risk of experiencing health and safety problems, one of which is musculoskeletal disorders. Aim: This study aimed to determine the prevalence and characteristics of musculoskeletal disorders among farmers in Aan Village, Klungkung Regency. Method: This researchs was a descriptive cross-sectional study. The population in this study was farmers in the Aan village, Banjarangkan, Klungkung, Bali. Data collection is done by filling in the NBM questionnaire by 80 respondents who were determined using simple random sampling technique. The study was conducted in May-September 2018. Results: The prevalence of farmers who experienced musculoskeletal disorders was 80%, and often felt in the right knee 40%, left knee 37.5%, waist 30.1%, right shoulder 15.1%, and left shoulder 12.6%. The age most experienced by musculoskeletal disorders is 46-55 years by 30%, which occurred in men (88%) and women (13%). Musculoskeletal disorders are more often experienced by farmers who have the last primary education (34%), not smoking (66%), have been a farmer for >10 years (89%), work >8 hours a day (55%), and work with the position of turning the body and holding back (100%). Conclusion: The prevalence of farmers who experience musculoskeletal disorders was 80%. Musculoskeletal disorders mostly occur in the right knee, left knee, waist, right shoulder, and left shoulder. Musculoskeletal disorders are more experienced by farmers aged 46-55 years, male farmers, having the last primary school education, not smoking, have been a farmer for >10 years, working >8 hours a day, and work with the position of turning the body and holding back.